Implementation of GMP and SSOP in Making Fish Chili Sauce - Darmadi, Ni Made; Edi, Dewa Gede Semara (PT FORMOSA CENDEKIA GLOBAL, 2024)
Chili Sauce is a famous food. Fish Chili Sauce made contains 10% fermented Tuna fish meat, to give a different taste. To get the quality of Fish Chili Sauce. The purpose of this study is to be able to apply the principles of Good Manufacturing Practice (GMP) and Sanitation Standard Operational Procedures (SSOP) in making fish Chili sauce. This study uses a Descriptive Method to see the Implementation of GMP and SSOP in Making Fish Chili Sauce. In each Principle of GMP and SSOP implementation, Objective and Subjective Microbial (TPC) and E.coli analysis will be carried out. The results of the study showed that the nutritional value of Fish Chili Sauce is Water 44.735%, Protein 4.595%, Fat 25.72%, Carbohydrate 4.1%, Ash 20.85%, pH 4.50 and TPC 2.4 x 10 4. With an Average Organoleptic Value of Taste 6.1 (Like), Aroma 6.5 (Like), Color 5.8 (Like), Texture and Overall Acceptance 6.2 (Like). The results of the Escherichia coli test from raw materials, equipment and also Fish Sambal showed Qualify.